Optimizing the Role of Libraries to Strengthening Literacy at MIN 1 Surabaya - Vita Sari, Nurul; Juhaeni, Juhaeni; Chasanah, Uswatun (Jurnal Tadwin, 2025)
Literacy serves as a crucial foundation for students' academic success and personal development, particularly at the elementary education level. This study aims to analyze the role of the library at Madrasah Ibtidaiyah Negeri (MIN) 1 Surabaya in supporting student literacy development. Employing a qualitative descriptive approach, this research examines literacy programs, resource availability, and perceptions of students and teachers regarding the library's function as a literacy center. The findings indicate that the MIN 1 Surabaya library implements various strategic initiatives, such as providing diverse reading collections, the "Read 15 Minutes" program, and digital literacy introductions, which significantly enhance students' reading interest and literacy skills. However, challenges related to the optimal utilization of information technology, collection updates, and limited human resources still need to be addressed to maximize the library's role. This research provides practical recommendations for developing the library as an effective literacy center in madrasahs.